Application of in vitro digestion and dialysability procedure for bioavailability evaluation of toxic elements in green leafy vegetables: a realistic health risk assessment by Monte Carlo simulation - Maha Abdallah Alnuwaiser; Hala Hazam Al-Otaibi; Refaat A. Eid; Shaban Ragab Ibrahim Sukkar; Nibal T. Al-Dalgamony; A. Al Solami; Ishraga Galal Eldin Abdalla Awad (Food Additives & Contaminants: Part A, 2026)

Iron-functionalized biochar and manure compost mitigate polyethylene microplastic toxicity in soil via enhanced performance of Solidago canadensis - Abdulmalik H. Altuwayjiri; Ishraga Galal Eldin Abdalla Awad; Malik Bader Alazzam; Saad Alrashdi; Maha Abdallah Alnuwaiser; Ahmed Mohajja Alshammari; Fathy Elsayed Abdelgawad (Journal of Environmental Chemical Engineering, 2026)

Passive and active seismics to identify geotechnical site characterization at industrial zone, Aswan, Egypt - Maha Abdelbaset; Abdelnasser Mohamed; Rashad Sawires; Awad A.A. Omran; Mostafa Thabet (Journal of Applied Geophysics, 2025)

Potentiality of Melatonin for Reinforcing Salinity Tolerance in Sorghum Seedlings via Boosting Photosynthetic Pigments, Ionic and Osmotic Homeostasis and Reducing the Carbonyl/Oxidative Stress Markers - Nesma M. Helal; Hani S. Saudy; Maha M. A. Hamada; Ahmed Abou El-Yazied; Hany G. Abd El-Gawad; Soumya Mukherjee; Salem Mesfir Al-Qahtani; Nadi Awad Al-Harbi; Salwa M. El-Sayed; Mohamed F. M. Ibrahim (Journal of Soil Science and Plant Nutrition, 2024)
Salinity stress has become a major threat to worldwide crop production. Exogenous melatonin (MT) has appeared as a promising treatment against salt stress in several plant species. However, MT effect on the tolerance of sorghum plants under different saline conditions (moderate and severe) remains ambiguous. This study was carried out to explore the impact of MT (0, 50, 100 and 200 µM) as a foliar application on sorghum seedlings grown under moderate and severe saline conditions using sodium chloride, NaCl (75 and 150 µM NaCl). Salinity treatments were applied as solution in sand medium in pots. The results demonstrated that rising salinity level negatively affected plant growth, photosynthetic pigments (chlorophylls and carotenoids), leaf water status and ionic homeostasis (sodium, potassium, and calcium ions). Applied-MT specifically at 100 or 200 µM enhanced the osmotic balance, cell membrane stabilizing and leaf relative water content. These effects were associated with an obvious restriction to the level of hydrogen peroxide, lipid peroxidation (malondialdehyde content) and methylglyoxal. Moreover, antioxidant activities of peroxidase, catalase, superoxide dismutase, and ascorbate peroxidase enzymes were modulated by MT treatments. Molecular docking modeling assessment illustrated top-ranked confirmations between MT and the target antioxidant enzymes. MT forms multiple hydrogen bonds with key amino acid residues for glycine (A: 162), tryptophan (A: 41), leucine (A: 165), tyrosine (A: 235) in the active site of ascorbate peroxidase. The alkyl interactions with leucine (A: 37), arginine (A: 38) and cysteine (A: 168) also contribute to its high affinity. Despite sorghum plant is commonly moderately tolerant to salinity stress, the results of this study confirmed its high sensitivity to a wide range of saline conditions at early growth stages. Melatonin spraying led to improvements in various morphological, physiological and biochemical mechanisms that harmonized together to confer stress resistance to salt-stressed sorghum seedlings.

Ecofriendly synthesis and nematicidal application of copper nanoparticles fabricated from Bacillus subtilis AM18, against root-knot nematode of cucumber - Ramadan M. El-Ashry; Maha M. Nader; Ashwag Shami; Manal A. Alduwish; Ahmed Ezzat Ahmed; Soha A. Alamoud; Aminah Allohibi; Fatimah S. Alqahtani; Amira M. Alghamdi; Alshaymaa I. Ahmed; Mokhles A. A. Hassan; Salonaz E. Awad; et al. (European Journal of Plant Pathology, 2024)

Discovery, synthesis and in combo studies of Schiff’s bases as promising dipeptidyl peptidase-IV inhibitors - Reema Abu Khalaf; Maha Awad; Luay Al-Essa; Sara Mefleh; Dima Sabbah; Eveen Al-Shalabi; Ihsan Shabeeb (Molecular Diversity, 2022)

Comparative study between human mesenchymal stem cells and etanercept as immunomodulatory agents in rat model of rheumatoid arthritis - Heba El-Gendy; Salah El-Deen Hawass; Manal Awad; Mona Ahmad Mohsen; Maha Amin; Hussein Abdelaziz Abdalla; Samah Fouad; Ahmed Lotfy (Immunologic Research, 2020)